2001
DOI: 10.1007/s002140100250
|View full text |Cite
|
Sign up to set email alerts
|

Electronic excitation of sulfur-organic compounds - performance of time-dependent density functional theory

Abstract: To de®ne the scope and limitations of the time-dependent density functional theory (TDDFT) method, spectral absorption data of a series of about 100 neutral or charged sulfur-organic compounds with up to 24 non-hydrogen atoms and up to four sulfur atoms were calculated in the near-UV, visible and IR regions. Although the theoretical vertical transition energies correspond only approximately to experimental absorption band maxima, the mean absolute deviation was calculated to be 0.21 eV (1600 cm )1 ). The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(64 citation statements)
references
References 59 publications
4
60
0
Order By: Relevance
“…By TD-DFT calculations converging to a C 2v boat geometry, Fabian assigned the weak absorption band around 368 nm to A 1 → B 1 transition (π → π * along x) and found only one state lying in the intense double structure (303/317 nm) corresponding to A 1 → B 2 transition (π → π * along y). 30 The oscillator strengths calculated by this TD-DFT study at 368 nm and ≈307 nm are very similar, which goes strongly against the experimental observations. [17][18][19][20] Andreu et al, as well by TD-DFT calculations still in C 2v symmetry, assigned the two most intense excitations to the 1 1 B 2 state transition at 317 nm and the 2 1 B 1 state transition at 303 nm.…”
Section: Introductionsupporting
confidence: 73%
“…By TD-DFT calculations converging to a C 2v boat geometry, Fabian assigned the weak absorption band around 368 nm to A 1 → B 1 transition (π → π * along x) and found only one state lying in the intense double structure (303/317 nm) corresponding to A 1 → B 2 transition (π → π * along y). 30 The oscillator strengths calculated by this TD-DFT study at 368 nm and ≈307 nm are very similar, which goes strongly against the experimental observations. [17][18][19][20] Andreu et al, as well by TD-DFT calculations still in C 2v symmetry, assigned the two most intense excitations to the 1 1 B 2 state transition at 317 nm and the 2 1 B 1 state transition at 303 nm.…”
Section: Introductionsupporting
confidence: 73%
“…Indeed, the TD-DFT transition energies are too large (by ca. 0.3-1.0 eV) in cyanines, and this conclusion has been reached through comparisons of both TD-DFT's E vertÀa with their highlycorrelated wavefunction counterparts [82,87] and TD-DFT's E AFCP with experimental references for fluoroborate emitters [88,89]. More puzzling is the fact that the errors seem to be almost independent of the selected XCF and that this error is not related to a multi-determinant nature.…”
Section: Cyanine Excited-statesmentioning
confidence: 80%
“…Both the canonical streptocyanines and the fluoroborate dyes (e.g., boron-dipyrromethene, BODIPY) belong to that class and it has been shown that they can hardly be modeled with adiabatic TD-DFT [33,[82][83][84][85][86][87][88][89][90][91][92][93]. Indeed, the TD-DFT transition energies are too large (by ca.…”
Section: Cyanine Excited-statesmentioning
confidence: 98%
“…These data show that they are rather comparable to the experimental values. TD‐PBE1PBE is better than the inspection of TD‐B3LYP/6‐31G* approach having a deviation of about 0.25 eV41. Figure 3 also shows that the emission spectra are underestimated, which is partly because of the neglect of the electron correlation of CIS approaches and its optimized structure in gas phase.…”
Section: Resultsmentioning
confidence: 95%